If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-3g + -9) = 0 Reorder the terms: -5(-9 + -3g) = 0 (-9 * -5 + -3g * -5) = 0 (45 + 15g) = 0 Solving 45 + 15g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + 15g = 0 + -45 Combine like terms: 45 + -45 = 0 0 + 15g = 0 + -45 15g = 0 + -45 Combine like terms: 0 + -45 = -45 15g = -45 Divide each side by '15'. g = -3 Simplifying g = -3
| 12-41=3(x-2)-8 | | 5x-7+8x= | | 45x^4-125=0 | | 6p-17=-33+2p | | 23=4-3n | | (3y-15)(y^2+4y-12)=0 | | 5-6x+9x=-15+5 | | 7+3r+9+6r= | | 9=-6(5)+b | | 25x^2+10x+4=0 | | g+7g= | | 82=5x | | x+45=2x-25 | | -2(-7-5b)= | | 8+7-4r-9r= | | 4*a+b=906.25 | | 7x^4+66x^2-40=0 | | 2x^2-3x+5=5 | | 10m=13 | | v-8=u | | 3s-18=24+9s | | 2r-25=-34+3r | | 7x^4+62x^2-9=0 | | 3y-7=-3y+-9 | | 81x^2+484=8 | | 4(x+3)=7x+15 | | X+7.5=-8 | | 7(3n+7(n+k)+2k)= | | V*2=80 | | 5+5b=2.5b | | y=(c-k)x+1 | | X+7.5=8 |